Polimorfismos de genes do sistema renina-angiotensina na doença arterial coronariana - Araújo, Messias Antônio de (2003)
The renin-angiotensin system (RAS) plays a central role in cardiovascular homeostasis. The angiotensin II is the key pepetide of the RAS and exerts its influence on the heart and blood vessels through its hemodynamic effects (via its influence on after-load and pre-load determining coronary vasoconstruction) and through the direct cell effects (via actions on cell proliferation). Numerous studies in the past ten years have demonstrated that the pharmacological inhibition of angiotensin converting enzyme and the block on the angiotensin II type 1 receptor (AT1R) have improved the outcome and the life quality in patients with systemic arterial hypertension, heart failure and ischaemic heart disease. These studies have suggested that the RAS is the highest cardiovascular risk determinant. Current results have demonstrated that the genetic factors may contribute to modulating the effects of the angiotensin II on coronary circulation physiology and on myocardial ischaemia. This study has taken some review of the RAS pathological and physiological characteristics, particularly on the genetic aspects and their consequences in the coronary artery disease (CAD). It is well proved by the literature that the classical risk factors to the CAD such as: CAD familiar antecedent, high leveis of total cholesterol, LDL cholesterol as well as triglycerides; low leveis of HDL cholesterol, tabagism, systemic arterial hypertension, diabetes mellitus, sedentarism and obesity may explain only 50% of its ethiology. So the modification of them may inhibit the development of the coronary atherosclerosis disease in only 40% of all patients. Therefore, the search for other mechanisms in the atherosclerosis genesis is necessary in order to clarify the association among several genetic factors and their phenotypic expression. In the first chapter it was evaluated the M235T variant of the angiotensinogen on CAD effect in 305 white people, the severity of the atherosclerosis disease in the coronary arteries and its risk in developing the acute myocardial infarction (AMI). There were 201 patients with proved CAD by a coronary angiography (obstructive lesion > 50%). From this group 110 patients were with AMI and 91 were without it. There were also 104 control individuais with angiographically normal coronary arteries. The CAD severity was analyzed by the number ofXV diseased vessels, atherosclerotic plaque morphology and the jeopardy score. The M235T angiotensinogen polymorphism was analyzed by the polymerdase chain reaction (PCR). The arterial hypertension, tabagism, diabetes mellitus, obesity and the high leveis of total and LDL cholesterol have predominated in the CAD patients. The genotypes frequencies TT, MT and MM of the AGT have been statistically different neither between CAD patients and controlled ones, nor between infarcted and non infarcted patients. The CAD and AMI relative risk (OR) analyzed between TT vs MM, MT vs MM and TT+MM vs MM genotypes presented no significance. The coronary atherosclerosis severity criteria in the CAD patients had no correlation with genotypes. These results were also found in the comparison between infarcted and noninfarcted groups. This study has concluded that there is no association between the M235T gene AGT polymorphism and CAD, neither with íts severity nor with the AMI. In the second chapter the association among polymorphism of angiotensin-converting enzyme (ACE) gene, CAD and acute myocardial infarction (AMI) in the same population of the study of the M235T variant of the AGT have also been investigated through PCR. Among the classical coronary risk factors only tabagism, diatetes mellitus, high total cholesterol and LDL leveis and artherial hypertension have predominated in the CAD group. Frequency distribution of genotypes between CAD groups and the Controls had statistic difference (p = 0.009); however, there was no risk of developing it when the DD II genotypes were compared (OR = 0.69; CI-95%: 0.36 - 1.34 and ID II (OR = 1.60; Cl - 95%: 0.81 - 3.14). In the comparison between the AMI patients and the controlled ones the results were similar; they were also statistically significant (p = 0.011) and there was no increasing risk of presenting AMI. Finally, it was concluded that there is no evidence of association between the l/D ACE gene polymorphism with CAD and AMI. In the third chapter it was analyzed the A1166C angiotensin type 1 gene receptor (AT1R) polymorphism association with the AMI and the CAD severity in 110 patients with AMI and significant coronary obstructive lesion (> 50%). TheXVI Controls were 104 individuais with normal coronary arteries. The polymorphism was determined through PCR in the peripheral blood leukocytes. Classical coronary risk factors have also been analyzed from these ones, only the tabagism has predominated in AG heterozygotes (p = 0.02). Genotypes distribution in infarcted patients was similar and there was no significant difference related to contrais. There was no AMI increasing risk in CC vs AA, AC vs AA and AA+AC vs AA genotypic comparisons. No severity criteria have had positive association with- genotypes. Therefore, it was concluded that there was no association between either A1166C AT1R poymorphism and AMI or with CAD severity. The fourth chapter has analyzed the interaction between M235T AGT gene, l/D ACE gene and A1166C AT1R gene polymorphisms and the AMI. There were 110 AMI patients with significant coronary artery lesion (> 50%) and 104 contrais with angiographycally normal coronary arteries. The polymorphisms were analyzed by PCR in DNA of peripheral blood leukocytes. The analysis of multiple logistic regression between the classical coronary factors and M235T of AGT, l/D of ACE and A1166C of AT1R polymorphisms have demonstrated that tabagism, family history, arterial hypertension and total cholesterol have been associated to the AMI risk. The M235T AGT genotypes frequencies were similar to each other between the infarcted patients and contrais; the risk of developing AMI was not different between them. There was not ACE genotypes association with the relative risk of developing AMI as well as the AT1R genotypes. Double homozygote combination of the AGT and ACE genes (MMII) has presented less AMI risk (OR = 0.34) and the genotypes combinations that include at least one unfavourable allele (T or D), the risk of presenting AMI was 2.92 times higher. Similar results were found in the AGT - AT1R genes associations with double homozygotes (MMAA) with less risk (OR = 0.38) and the other unfavourable alleles combinations with risk of 2.63 fold greater. In the ACE — AT1R association the risk of double homozygotes was also lower (OR = 0.37) and the other unfavourable alleles combinations have presented risk 2.68 times higher. There was not any positive interaction when the three gene genotypes were associated among themselves. In conclusion there is higher risk of AMI wheneverXVII there is unfavourable alleles gene to gene association and lower risk in the double favourable homozygote association of polymorphisms M235T of AGT, l/D of ACE and A1166C of AT1R. There are several potential molecular mechanisms in CAD, however it is getting more and more evident their interactions in this complex disease of high prevalence and clinicai, economic and social consequences have been quite relevant. The most ambicious goal in preventive Medicine is the establishment of genetic tests in the prevention of myocardial infarction while in clinicai Medicine it is the genetic therapy that will be available to clinicai use the soonest it seems to be. So it becomes an important tool in order that the cardiologist adopts the most adequate treatment for his patient.